2021
DOI: 10.1016/j.jamcollsurg.2021.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Does Preoperative Calcium and Calcitriol Decrease Rates of Post-Thyroidectomy Hypocalcemia? A Randomized Clinical Trial

Abstract: BACKGROUND: Postoperative hypocalcemia is the most common complication after thyroidectomy. Postoperative supplementation with calcium and calcitriol reduces its occurrence; however, prophylactic preoperative supplementation has not been studied systematically. The primary objective of this study was to determine whether pre- and postoperative calcium and calcitriol supplementation reduces postoperative hypocalcemia after total thyroidectomy compared with postoperative supplementation alone. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…Interestingly, just before releasing our results, two newly emerged published studies have demonstrated various and even opposite results (17,18). The key reason for the opposite conclusion lies in analyzing the calcium levels based on further subgrouping postoperative PTH levels.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Interestingly, just before releasing our results, two newly emerged published studies have demonstrated various and even opposite results (17,18). The key reason for the opposite conclusion lies in analyzing the calcium levels based on further subgrouping postoperative PTH levels.…”
Section: Discussionmentioning
confidence: 84%
“…In our study, all 172 patients received bilateral central compartment neck dissection. In contrast, only 11.0% [9 out of 82, reported by Donahue et al (17)] patients and 27.7% [13 out of 47, reported by Shonka et al ( 18)] underwent central compartment neck dissection. In this setting, patients in our study had higher rates of transient hypoparathyroidism and symptomatic hypocalcemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of symptomatic hypocalcemia in patients with Basedow-Graves disease (GD) was 50.0% for those clinically treated and 43.0% for those not treated, with no statistical difference between them (Bugălă et al, 2022;Palmhag et al, 2021;Şahbaz et al, 2018;Soylu & Teksoz, 2020;THAKUR, 2021). In contrast, Donahue et al, (2021) did not consider hyperthyroidism as a predictive factor for postoperative hypocalcemia, but empirically treated all patients postoperatively with calcium carbonate and/or vitamin D (Donahue, Pantel, Yarlagadda, & Brams, 2021). Phookan et al, (2021), Moran et al, (2020) and Wojtczak et al, (2018) commented that toxic goiter, as it is more vascularized, contributes to increased perioperative bleeding, reducing the visibility of the surgical field (Moran et al, 2020;Phookan et al, 2021;Wojtczak, Aporowicz, Kaliszewski, & Bolanowski, 2018).…”
Section: Hyperthyroidism and Hypothyroidismmentioning
confidence: 99%